Standardized treatment planning methodology for passively scattered proton craniospinal irradiation - Giebeler, Annelise (BioMed Central, 2013)
BACKGROUND: As the number of proton therapy centers increases, so does the need for studies which compare proton treatments between institutions and with photon therapy. However, results of such studies are highly dependent on target volume definition and treatment planning techniques. Thus, standardized methods of treatment planning are needed, particularly for proton treatment planning, in which special consideration is paid to the depth and sharp distal fall-off of the proton distribution. This study presents and evaluates a standardized method of proton treatment planning for craniospinal irradiation (CSI). METHODS: We applied our institution’s planning methodology for proton CSI, at the time of the study, to an anatomically diverse population of 18 pediatric patients. We evaluated our dosimetric results for the population as a whole and for the two subgroups having two different age-specific target volumes using the minimum, maximum, and mean dose values in 10 organs (i.e., the spinal cord, brain, eyes, lenses, esophagus, lungs, kidneys, thyroid, heart, and liver). We also report isodose distributions and dose-volume histograms (DVH) for 2 representative patients. Additionally we report population-averaged DVHs for various organs. RESULTS: The planning methodology here describes various techniques used to achieve normal tissue sparing. In particular, we found pronounced dose reductions in three radiosensitive organs (i.e., eyes, esophagus, and thyroid) which were identified for optimization. Mean doses to the thyroid, eyes, and esophagus were 0.2%, 69% and 0.2%, respectively, of the prescribed dose. In four organs not specifically identified for optimization (i.e., lungs, liver, kidneys, and heart) we found that organs lateral to the treatment field (lungs and kidneys) received relatively low mean doses (less than 8% of the prescribed dose), whereas the heart and liver, organs distal to the treatment field, received less than 1% of the prescribed dose. CONCLUSIONS: This study described and evaluated a standardized method for proton treatment planning for CSI. Overall, the standardized planning methodology yielded consistently high quality treatment plans and perhaps most importantly, it did so for an anatomically diverse patient population.